Sustentabilidade ESG (Environmental, Social, and Corporate Governance): a indústria de petróleo e gás como atores fundamentais na transição energética - Almeida, Juan Felipe Pereira de (Universidade Federal de São Carlos, 2024)
The history of humanity is deeply linked to the evolution of the collective use of energy, and it is essential to balance production systems for sustainable development. This work highlights the strategic contribution of the Brazilian oil and natural gas industry in the construction of a low-carbon energy matrix, pointing out as the main finding the importance of this transition to more sustainable energy sources, such as solar energy, green hydrogen and carbon capture technologies. The research sought to address the main arguments of best relevance to the development of the work, listing a methodological approach through the literature review to build critical thinking to reach plausible results on the subject, integrating the economy and the environment to demonstrate that the energy transition, driven by climate change, is fundamental to face global challenges and ensure a balanced future.
Sustainability ESG (Environmental, Social, and Corporate Governance): a oil and gas industry as key actors in energy transition
Keywords: Matriz energética; Captura de carbono; Energias renováveis; Impactos ambientais; Soluções sustentáveis.; Energy matrix; Carbon capture; Renewable energies; Environmental impacts; Sustainable solutions; ENGENHARIAS